How have state aid rules been used to counter crises? - Paukku, Eelis; Siikavirta, Kristian (Edita, 2022)
When a state runs into a crisis, public authorities are called for help. European State Aid rules generally prohibit the Member States from using subsidies. However, the European Commission has the power to decide which subsidies to allow in the Member States. This paper makes an analytical examination of how the Commission has used that power in six crises during the last four decades. They are the Chernobyl disaster in 1986, the mad cow disease crisis in 1996, the global financial crisis in 2007–2008, the European debt crisis in 2010–2014, the eruptions of Eyjafjallajökull in 2010, and the COVID-19 crisis 2020-ongoing. The Commission cannot demand the Member States to use state aid in crises, but our paper concludes that the Commission has increased its activity and has taken different real-life circumstances into consideration.

Kun valtio ajautuu kriisiin, viranomaisia kutsutaan apuun. EU:n valtiontukisäännökset kieltävät yleensä jäsenvaltioita käyttämästä valtionavustuksia. Euroopan komissiolla on kuitenkin valta päättää, mitkä avustukset sallitaan jäsenvaltioissa. Tässä kirjoituksessa tarkastellaan analyyttisesti, kuinka komissio on käyttänyt tätä valtaa kuudessa kriisissä viimeisen neljän vuosikymmenen aikana. Kriisit, joita kirjoituksessa käsitellään, ovat Tšernobylin katastrofi vuonna 1986, hullun lehmän taudin aiheuttama kriisi vuonna 1996, maailmanlaajuinen finanssikriisi vuosina 2007–2008, Euroopan velkakriisi vuosina 2010–2014, Eyjafjallajökullin tulivuorenpurkaus vuonna 2010 sekä COVID-19 kriisi, joka alkoi vuonna 2020 ja on yhä meneillään. Komissio ei voi vaatia jäsenvaltioita käyttämään valtiontukea kriiseissä, mutta tutkimuksessa esitetyn päätelmän mukaan komissio on lisännyt aktiivisuutta ja ottanut huomioon erilaiset tosielämän olosuhteet.
Keywords: Euroopan komissio; Euroopan unioni; Kriisinhallinta; Valtionavustus; COVID-19; fi=Julkisoikeus|en=Public Law|